Private schools as drivers of social segregation: Why private schools should be regulated - Rita Nikolai; Marcel Helbig (On Education. Journal for Research and Debate, 2021)
In international comparison, the share of pupils enrolled in private schools is expanding and the access to private schools is socially unequal. There is a need for the regulation and control of private schools. Focusing on Germany, this contribution discusses how such a regulation might look like without endangering the freedom for the foundation and pedagogical operation of private schools.
Keywords: 300; private schools; public subsidies; school choice; social segregation